Mortgage Market Analysis: Domestic and International Experience - Nataliia Sirenko; Kateryna Kazemyrchyk; Kateryna Mikuliak (Облік і фінанси, 2023)
In the conditions of an economic crisis, the activation of economic activity through mortgage lending becomes crucial, and the study of the development of the mortgage market in the world is necessary for a comprehensive understanding of its impact on social, economic, and financial growth. It is also essential for determining optimal management strategies for the housing sector in a specific country. The article aims to substantiate the features of the functioning of the mortgage market in the world and in Ukraine. Investigating the peculiarities of domestic and foreign mortgage markets, the authors used a statistical method to analyze the mortgage market and government mortgage credit programs in Ukraine and worldwide. Empirical evidence in the research includes data from the Ukrainian Financial Housing Company, the Ministry of Finance of Ukraine, and the Diya platform, presented using a graphical method. Abstraction, analysis, and synthesis methods formed the basis for developing recommendations for improving government programs for developing the mortgage market for housing in the world and in Ukraine. The dynamics of mortgage loans issued in Ukraine for 2019–2022 indicate a decline in mortgage loan issuance due to unstable political and economic situations. It was revealed that the restoration of mortgage lending in Ukraine is facilitated by the Ukrainian government's eOselya program, which is aimed at providing citizens with affordable housing. The specifics of mortgage lending in different countries worldwide are disclosed. The overall trend of diversity in mortgage lending conditions in the European Union indicates significant differences in approaches to housing loans in different countries. However, some positive characteristics of the mortgage market development in the EU can serve as valuable experience for reforming Ukraine's national mortgage lending market. Among them are financial and investment capacities, low cost of loans, socio-legal protection, macroeconomic stability, transparency, informational clarity, and unified regulatory approaches.